Basic Information and Communication Technology Skills among Canadian Immigrants and Non-Immigrants - N. T. Khuong Truong; Arthur Sweetman (Institute of Labor Economics (IZA), 2018)
Male immigrants are observed to be disproportionately employed in ICT information and communication technology (ICT) industries and occupations. A measure of basic ICT skills is employed to document differences in skill levels and labour market earnings across immigration classes and categories of Canadians at birth. Adult immigrants, including those assessed by the points system, are found to have lower average ICT scores than Canadians at birth, although the rate of return to ICT skills is not statistically different between them. Immigrants who arrive as children, and the Canadian-born children of immigrants, have similar outcomes to the Canadian-born children of Canadian-born parents.
Keywords: J24; J31; 330; information and communication technologies (ICT); skills; immigration; PIAAC; problem-solving in technology-rich environments (PSTRE); digital literacy; problem-solving; skill shortage